SUPPLY CHAIN MANAGEMENT PERFORMANCE OF CORN IN EAST LOMBOK (KINERJA MANAJEMEN RANTAI PASOK JAGUNG DI LOMBOK TIMUR) - Tajidan @ (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2015)
ABSTRACT The improvement of corn farmer welfare is a must that involves struggle by them to keep up their enthusiasm in corn farming. A solution for this challenge is by applying supply chain management. The objectives of research are (1) to analyze supply chain management performance of the corn from producers to cunsumers, and (2) to understand relationship of supply chain management with farmer welfare and corn consumers satisfaction. Respondents of this research are farmers, intermediate traders, and corn consumers. The farmers were selected using simple random sampling technique, while intermediate traders and corn consumers were selected using snowball sampling technique. Narrative descriptive analysis and Spearman Rank Correlation are used to analyze the data. It is concluded that (1) Supply Chain Management Performance of the corn is 3.212 in average and remaining between 2.6 and 3.6 and it is in the “almost good“ category and (2) Supply Chain Management is related positively and significantly to farmers welfare and corn consumers satisfaction. ABSTRAK Perbaikan kesejahteraan petani jagung merupakan suatu keharusan mesti diperjuangkan oleh semua pihak agar mereka tetap bersemangat di dalam berusahatani jagung. Salah satu solusi yang ditawarkan bagi pemangku kepentingan adalah menerapkan manejemen rantai pasok (suplly chain management). Tujuan dari penelitian ini adalah : (1) menganalisis keragaan manajemen rantai pasok jagung dari produsen sampai dengan konsumen; (2) menganalisis hubungan manajemen rantai pasok dengan kesejahteraan petani dan kepuasan konsumen pengguna jagung. Resopnden dalam penelitian ini adalah para petani, pedagang perantara dan konsumen pengguna jagung yang dipilih dengan teknik proporsional snowball sampling. Analisis data menggunakan deskriptif naratif dan korelasi rank spearman. Kesimpulan yang diperoleh dari hasil penelitian ini adalah : (1) Keragaan manajemen rantai pasok jagung rata-rata 3,212 berada pada kisaran antara 2,6 dan 3,6 dengan kategori hampir baik; (2) Manajemen rantai pasok berhubungan positif dan signifikan dengan kesejahteraan petani dan kepuasan konsumen pengguna jagung.